2004
DOI: 10.1590/s0074-02762004000100014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytotoxic necrotizing factor types 1 and 2 among fecal Escherichia coli isolates from brazilian children with and without diarrhea

Abstract: The enteropathogenic role of cytotoxic necrotizing factor (CNF)-producing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…No cnf2 or cnf3 genes, which were first observed in E. coli strains isolated from animals (12, 45), were detected in our human strains, a finding consistent with the absence or very weak prevalence of these genes observed in previous studies (9,12,32,37,55,63,64). These results suggest that cnf2-and cnf3-positive strains are almost entirely absent in humans and thus are probably involved only in animal diseases.…”
Section: Resultssupporting
confidence: 91%
“…No cnf2 or cnf3 genes, which were first observed in E. coli strains isolated from animals (12, 45), were detected in our human strains, a finding consistent with the absence or very weak prevalence of these genes observed in previous studies (9,12,32,37,55,63,64). These results suggest that cnf2-and cnf3-positive strains are almost entirely absent in humans and thus are probably involved only in animal diseases.…”
Section: Resultssupporting
confidence: 91%
“…15,19 Nevertheless, recent studies did not find an exclusive association with disease and concluded that necrotoxic E. coli may be part of the normal gastrointestinal flora. 24 In the tiger lung, predominantly macrophages were observed in the lesions, which is in contrast with the findings reported in other animals, in which neutrophils were the main inflammatory cell in the alveolar spaces.…”
Section: 17contrasting
confidence: 75%
“…Escherichia coli strains carrying cnf -1 have been isolated from humans with urinary tract infection and, sporadically, from feces of children with diarrhea 15,19 . Nevertheless, recent studies did not find an exclusive association with disease and concluded that necrotoxic E. coli may be part of the normal gastrointestinal flora 24 …”
mentioning
confidence: 99%
“…CNF1 strains have mostly been isolated from extraintestinal infections from humans with urinary tract infections (UTIs) and occasionally children with diarrhoea. The majority of CNF2 strains have been isolated from calves with septicaemia or diarrhoea [13].…”
Section: Introductionmentioning
confidence: 99%